Introduction to Hospitality Global Edition - Walker, John (Pearson, 2021)
"For introductory courses in hospitality. Introduction to Hospitality is a lively, comprehensive survey of the world's largest industry - hospitality. Students explore the vibrant inner workings of each hospitality segment, including hospitality and lodging; beverages, restaurants, and managed services; tourism, recreation, attractions, clubs, and gaming; assemblies, events, and attractions; and managerial areas of the hospitality industry. The 8th Edition highlights a range of issues shaping the future of each segment of the hospitality industry.
Keywords: Management; Hotelgewerbe; Gastgewerbe; Vocational / Professional Studies; Careers; Culinary Arts and Hospitality Management